Physical and hydraulic properties of soil in flooding areas, Shah Alam, Malaysia - Riyan Subekti,; Norsyafina Roslan,; Nor Shahidah Mohd Nazer, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Floods is a major concern in Shah Alam, Malaysia, affecting communities in terms of duration, frequency and impact. Knowing the nature of the soil and the rate of infiltration can help predict the rate at which water enters the soil, thus, providing information for better flood management. The purpose of this study was to characterize the physical and hydraulic properties of soil in flooding areas. Natural land areas along the banks of Sungai Klang was selected, where this river plays an important role in flooding in Shah Alam. The subsurface lithological layer was developed from the interpretation of borehole log data. The disturbed sample was taken using hand augers until it reached the water table, and a standpipe was installed at each location for water table measurement. The infiltration rate is determined using a double-ring infiltrometer. The results showed that the soil types in the eight study locations were dominated by sand and silt, with shallow water tables. The groundwater level fluctuated during high and low rainfall. Infiltration rates vary, with L1, L2, and L6 having rates of 108 mm/h to 179 mm/h, while L3, L4, L5, L7, and L8 have rates from 60 mm/h to 75 mm/h. Time to soil saturation varies. In dry conditions, all locations take 10 to 25 h for soil to reach saturation level except at L6. During the rainy season, saturation was reached in 2 to 5 h, except for L1, L5, L7 and L8, which took 7 to 10 h.